A novel K-ion battery: hexacyanoferrate(ii)/graphite cell. Issue 9 (16th February 2017) - Bie, Xiaofei; Kubota, Kei; Hosaka, Tomooki; Chihara, Kuniko; Komaba, Shinichi
Abstract : The four volt K-ion battery is demonstrated as a possible alternative to 4 volt Li-ion battery. Abstract : Recently, research on novel and low cost batteries has been widely conducted to realize large-scale energy storage systems. However, few of the battery systems have delivered performance equal to that of Li-ion batteries. Herein, we propose non-aqueous K-ion batteries by developing hexacyanoferrate(ii ) compounds (so-called Prussian blue analogues), K1.75 Mn[Fe II (CN)6 ]0.93 ·0.16H2 O and K1.64 Fe[Fe II (CN)6 ]0.89 ·0.15H2 O, as affordable positive electrode materials. In particular, K1.75 Mn[Fe II (CN)6 ]0.93 ·0.16H2 O prepared by a simple precipitation process delivers a high capacity of 141 mA h g −1 at 3.8 V as the average operating potential, resulting in a comparable energy density to that of LiCoO2, with excellent cyclability and rate performance in K half-cells. Operando X-ray diffraction measurements reveal that the excellent electrochemical performance of this material is attributed to its open and flexible framework, which can realize fully reversible K + extraction/insertion and a structural change from monoclinic to tetragonal via cubic phases. For the first time, we demonstrate an inexpensive high-voltage K-ion full cell with a K1.75 Mn[Fe(CN)6 ]0.93 ·0.16H2 O/graphite configuration to prove its feasibility as a new promising battery system for an environmentally friendly future.